Noggin resistance contributes to the potent osteogenic capability of BMP9 in mesenchymal stem cells. Issue 11 (16th July 2013) - Wang, Yi; Hong, Siqi; Li, Ming; Zhang, Jiye; Bi, Yang; He, Yun; Liu, Xing; Nan, Guoxin; Su, Yuxi; Zhu, Gaohui; Li, Ruidong; Zhang, Wenwen; et al.
Abstract: Mesenchymal stem cells (MSCs) are multipotent progenitors and can differentiate into osteogenic, chondrogenic, and adipogenic lineages. Bone morphogenetic proteins (BMPs) play important roles in stem cell proliferation and differentiation. We recently demonstrated that BMP9 is a potent but less understood osteogenic factor. We previously found that BMP9‐induced ectopic bone formation is not inhibited by BMP3. Here, we investigate the effect of BMP antagonist noggin on BMP9‐induced osteogenic differentiation. BMP antagonists noggin, chording, gremlin, follistatin, and BMP3 are highly expressed in MSCs, while noggin and follistatin are lowly expressed in more differentiated pre‐osteoblast C2C12 cells. BMP9‐induced osteogenic markers and matrix mineralization are not inhibited by noggin, while noggin blunts BMP2, BMP4, BMP6, and BMP7‐induced osteogenic markers and mineralization. Likewise, ectopic bone formation by MSCs transduced with BMP9, but not the other four BMPs, is resistant to noggin inhibition. BMP9‐induced nuclear translocation of Smad1/5/8 is not affected by noggin, while noggin blocks BMP2‐induced activation of Smad1/5/8 in MSCs. Noggin fails to inhibit BMP9‐induced expression of downstream targets in MSCs. Thus, our results strongly suggest that BMP9 may effectively overcome noggin inhibition, which should at least in part contribute to BMP9's potent osteogenic capability in MSCs. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1796–1803, 2013